Differences of Respiratory Rate Between Salbutamol and Aminofilin in Exacerbation Asthma - Amelia Lorensia; Zullies Ikawati; Tri Murti Andayani; Daniel Maranatha (Indonesian Journal of Pharmaceutical Science and Technology, 2020)
Exacerbation of asthma is a progressive step in progressive breathing, coughing, wheezing, breathing. In Indonesia salbutamol nebulation is used for the therapy of the first exacerbation attack. In addition, intravenous aminophylline is also recommended as a therapy, even if the use of aminophylline abroad is reduced due to its smaller effectiveness and often leads to greater unwanted reaction events. The effectiveness of asthma exacerbation therapy needs to be monitored and one of the monitoring parameters that is easily seen is the rate of breath.The aim of this study was to investigate the difference in respiratory rate values using salbutamol nebulisation and intravenous aminophylline in patients with asthma exacerbations in hospitals in Surabaya. The research was conducted by using quasi experimental method and data collection by purposive sampling. Analysis of the data to be used is a independent t-test. The results showed that the salbutamol group decreased respiratory rate by 50.00%, there were also patients who experienced an increase of breath rate of 13.64%. In the aminophylline group experienced a decrease in respiratory rate of 43.75% with an increase of breath rate of 18.75%. From the results of the study, it is necessary to monitor the effectiveness and the need to monitor the unwanted reactions of both treatments so that the therapies produced in the treatment of asthma exacerbations are more effective.Key words: Aminophylline, exacerbation asthma, respiratory rate, salbutamol